Cell Cycle Progression Score, but Not Phosphatase and Tensin Homolog Loss, Is an Independent Prognostic Factor for Metastasis in Intermediate- and High-risk Prostate Cancer in Men Treated With and Without Salvage Radiotherapy. Issue 6 (25th December 2022) - Trock, Bruce J.; Jing, Yuezhou; Mabey, Brent; Sangale, Zaina; Lenz, Lauren; Haney, Nora; Vidal, Igor; Glavaris, Stephanie A.; Guner, Gunes; Ertunc, Onur; Kulac, Ibrahim; Baena Del Valle, Javier A.; et al.
Abstract : Purpose: The prognostic value for metastasis of the cell-cycle progression score and phosphatase and tensin homolog haven't been evaluated jointly in contemporary men with exclusively intermediate- or high-risk prostate cancer. We evaluated associations of cell-cycle progression and phosphatase and tensin homolog with metastasis-free survival in contemporary intermediate/high-risk prostate cancer patients overall, and intermediate/high-risk men receiving salvage radiotherapy. Materials and Methods: In a case-cohort of 209 prostatectomy patients with intermediate/high-risk prostate cancer, and a cohort of 172 such men who received salvage radiotherapy, cell-cycle progression score was calculated from RNA expression, and phosphatase and tensin homolog was analyzed by immunohistochemistry. Proportional hazards regression, weighted for case-cohort design or unweighted for the salvage radiotherapy cohort, was used to evaluate associations of cell-cycle progression, phosphatase and tensin homolog with metastasis-free survival. Improvement in model discrimination was evaluated with the concordance index. Results: In the case-cohort 41 men had metastasis, and 17 developed metastasis in the salvage radiotherapy cohort, at median follow-up of 3 and 4 years, respectively. For both case-cohort and salvage radiotherapy cohort, cell-cycle progression was independently associated with metastasis-free survival after adjustment for Cancer of the Prostate Risk Assessment Post-Surgical: hazard ratio (95% confidence interval) = 3.11 (1.70-5.69) and 1.85 (1.19-2.85), respectively. Adding cell-cycle progression to Cancer of the Prostate Risk Assessment Post-Surgical increased the concordance index from 0.861 to 0.899 (case-cohort), and 0.745 to 0.819 (salvage radiotherapy cohort). Although statistically significant in univariate analyses, phosphatase and tensin homolog was no longer significant after adjustment for Cancer of the Prostate Risk Assessment Post-Surgical. Analysis of interaction with National Comprehensive Cancer Network risk group showed that cell-cycle progression had the strongest effect among unfavorable intermediate-risk men. Conclusions: In the first study to evaluate metastasis risk associated with cell-cycle progression and phosphatase and tensin homolog in exclusively intermediate/high-risk prostate cancer, and in such men with salvage radiotherapy, cell-cycle progression but not phosphatase and tensin homolog was associated with significantly increased 2- to 3-fold risk of metastasis after Cancer of the Prostate Risk Assessment Post-Surgical adjustment.